Evaluación del daño por corrosión del acero AISAI SAE 4330 en contacto con un lodo de perforación (2015)
Drilling fluids also known as drilling muds play a very important role in the oil and gas industry. Muds can be oil-based or water-based. Oil-based fluids have limited application due environmental problems. On the other hand, water-based muds are usually corrosive. Drilling muds have different functions such as the transport of drill cuttings to the surface, cooling, cleaning and lubrication of the drill bit and the drill collars as well as maintaining the stability of the well and the prevention of any escape of gas or oil. It is expected that the mud will not cause excessive wear or corrosion to the materials used in the drillstring. In this study the corrosion of the AISI 4330 steel in contact with a water-based drilling mud was evaluated using the electrochemical techniques Tafel extrapolation and impedance spectroscopy. The corrosion tests were performed at temperatures of 30, 45 and 60 ° C and rotation rates of 1000, 2000, 3000 rpm using a rotating cylinder electrode (ECR). Therefore, downhole and surface service conditions were simulated. It was found that the rotation rate is the most influential variable on the corrosion rate of the aisi 4330 steel. With increasing the rotation rate the corrosion current density increased and the polarization resistance decreased, consequently, the corrosion rate of the investigated steel increased